Evaluation of serum c-peptide levels in type 2 diabetics in Punjabi population - Deep, Hardeep Singh; Singh, Barjinder Pal; Singh, Shalinder Pal (International Journal of Advances in Medicine, 2017)
Background: Diabetes mellitus is a chronic metabolic and endocrine disorder characterized by chronic hyperglycemia with disturbances of carbohydrate, fat and protein metabolism resulting from defects in insulin secretion, insulin action or both. It is a major cause of mortality and morbidity worldwide. Human insulin and c-peptide are synthesized as a single polypeptide chain known as Proinsulin in the pancreatic beta cells. Serum insulin measurement gives a wrong value of insulin secretion, because insulin after its secretion into the portal vein, passes through the liver where approximately 50% of the delivered insulin is extracted. The measurement of C-peptide, thus provides a better index of endogenous insulin production and pancreatic beta cell function than insulin measurements. Methods: The present study was conducted on 100 adult patients of type 2 diabetes mellitus presenting in OPD and emergency or admitted in Sri Guru Ram Das Institute of Medical Sciences and Research, Amritsar. Type 1 diabetic patients, pregnant females with diabetes, patients presenting with acute infections, septicaemia, patients with acute or chronic pancreatitis, patients with pancreatic carcinoma were excluded from the study. In this study C-Peptide levels were estimated by DRG C-peptide ELISA method. Results: In our study, 38% patients had adequate insulin reserve (Normal C-peptide levels). Only 2% patients had poor insulin reserve (C-peptide levels below normal). 60% patients had c peptide levels more than normal, indicating insulin resistance. Increase in fasting c-peptide levels were associated with increased fasting plasma glucose (due to insulin resistance). A positive correlation exists in our study with r value of 0.523. Conclusions: As majority of patients with elevated FBS and fasting c-peptide were obese, our study infers that obese are more insulin resistant than non-obese. Since c-peptide levels assess the endogenous insulin reserve, it will also be helpful to alter the treatment modality based on it. So, routine c-peptide testing should be done in patients with poor glycaemic control to modify treatment modality accordingly.